Strategi Telecommuting Work: Sejauh Mana Pengaruhnya terhadap Kepuasan Kerja dan Kinerja - Suryani, Irma; Amalia, Rizki; Zainul, Zaida Rizqi; Rahmani, Sari; Riamanda, Irin (Jurnal Manajemen dan Keuangan, 2023)
This study focuses on the relationship between telecommuting work with performance, job satisfaction, and work-life balance. This research is important because the telecommuting policy has been taken by many institutions considering the advantages of this policy are very efficient, such as reducing costs, time, and space. This study aims to provide an overview of the extent to which the impact of telecommunications works on the behavior of workers, especially workers in a university environment. Using descriptive research methods, this research used online questionnaires distributed to 174 lecturers at Syiah Kuala University. The data was analysed using SEM AMOS to see and test the relationship between variables. The results showed that telecommuting work showed a positive and significant relationship to job satisfaction, work-life balance, and performance. Likewise, the relationship between work-life balance, satisfaction, and performance showed positive and significant results. Finally, work-life balance and job satisfaction mediate the relationship between telecommuting work and performance. Keywords: Telecommuting Work, Job Performance, Job Satisfaction, Work-Life Balance.